PERCEPTION AND PRACTICE OF ENERGY DRINKS CONSUMPTION BY MEDICAL STUDENTS OF WAH MEDICAL COLLEGE: Energy Drinks Consumption - Imran, Shezadi Sabah; Khan, Khola Waheed; Maqsood, Imrana; Mehmood, Muqadsa; Tallae, Tallisa (Pakistan Armed Forces Medical Journal, 2018)
Objectives: To determine the frequency of use of energy drinks, to assess gender, residence and year of education difference with the usage of energy drinks and the perception of students about benefits of energy drinks consumption. Study Design: Cross sectional study. Place and Duration of Study: Wah Medical College (WMC), from Jan to Jun 2016. Material and Methods: The 369 students of WMC from all years of MBBS course were selected through convenient sampling technique. After obtaining verbal consent the data were collected using a self administered closed ended questionnaire and analyzed by using SPSS version 19. Results: The frequency of consumption of energy drinks among students of WMC was 34%. Red bull was the most common (48%) brand used by them. Significant differences were found between usage of energy drinks with gender (<0.001), but insignificant difference with residence (0.06) and year of education (0.37). Out of 369 students, 310 (81.6%) students thought that energy drinks help them to stay awake longer and 73-75% were of the opinion that its use improved their concentration and mental performance. Conclusion: It was concluded that the consumption of energy drinks was high among medical students and most of them were male students. The most well-liked energy drink was Red bull and they believed that energy drinks helped them to stay awake longer, reduced tiredness and improve mental performance.